KULINER INDONESIA SEBAGAI ALAT DIPLOMASI BUDAYA (STUDI KASUS DI KOTA TORONTO) - M Aditya Tri Darma; Heri Nuryanto (Journal of Innovation Research and Knowledge, 2025)
One of the important strategies in cultural diplomacy is culinary diplomacy, which uses food as a means to introduce a country's values and traditions. This study looks at how Indonesian cuisine can serve as a tool of cultural diplomacy in Toronto, Canada, by showing opportunities and problems in promoting Indonesian cuisine. Data was collected from interviews with culinary entrepreneurs, members of the diaspora community, and consulate representatives through a qualitative approach and case studies. The results of the study show that traditional Indonesian foods, such as rendang and satay, serve as an effective cultural link and increase the positive perception of Indonesia in the Toronto community. However, culinary diplomacy efforts are hampered by issues such as the lack of culinary promotion standards and the limited number of restaurants in Indonesia. As a result, it is recommended that the government and diaspora communities work together to find and promote iconic foods that can increase understanding of Indonesian cuisine around the world. This research opens our eyes to the role of culinary in cultural diplomacy and how Indonesia can strengthen its international presence